2005
DOI: 10.1890/04-1726
|View full text |Cite
|
Sign up to set email alerts
|

Local Factors and Colonist Dispersal Influence Crustacean Zooplankton Recovery From Cultural Acidification

Abstract: We investigated the roles of local environmental conditions and dispersal limitation in zooplankton recovery from acidification in Swan Lake, Ontario, a historically acidified, metal‐contaminated lake. We hypothesized that local environmental conditions (pH and the presence of resident, acid‐tolerant zooplankton) would limit the establishment of several zooplankton colonist species. We tested this in a factorial mesocosm experiment that ran for 32 days during the mid summer. Ambient pH (5.6) reduced the abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 50 publications
(50 reference statements)
1
52
0
Order By: Relevance
“…Also, the occasional success of adult colonists in this study and others (e.g. Binks et al 2005) shows that colonisation by mature zooplankton is possible. Further experiments involving the addition of colonists to enclosures with and without resident zooplankton would be necessary to determine whether biotic factors (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Also, the occasional success of adult colonists in this study and others (e.g. Binks et al 2005) shows that colonisation by mature zooplankton is possible. Further experiments involving the addition of colonists to enclosures with and without resident zooplankton would be necessary to determine whether biotic factors (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Predation and competition are likely to have important effects on the zooplankton community composition in new ponds. It is possible that competition with species that established populations early on delayed colonization by other species present in nearby source populations, just as acidtolerant species established in acidified lakes delay the recovery of acid-sensitive species after restoration of normal pH (Binks et al, 2005;Frost et al, 2006). However, little is known about the interactions between the species recorded in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Biological resistance could also play a role by preventing establishment in an otherwise hospitable environment. For instance, priority effects can allow the resident zooplankton community to inhibit further colonization through resource monopolization (Boileau et al 1992;Lukaszewski et al 1999;Shurin 2000;De Meester et al 2002;Binks et al 2005). Predation by macroinvertebrates has also been shown to significantly reduce zooplankton abundance, diversity, and species richness in some acid-recovering lakes (Arnott et al 2006) and can play a role in restricting colonization when fish are not present (Arnott and Vanni 1993; but see Shurin 2001).…”
Section: Consequences Of Canoe-mediated Dispersalmentioning
confidence: 99%
“…Several studies have identified a number of local exclusion mechanisms at work even in the face of frequent dispersal, including biological resistance from native and non-native predatory macroinvertebrates (Arnott and Vanni 1993;Keller et al 2002;Arnott et al 2006;Strecker and Arnott 2010) and competitive interactions with the resident zooplankton community (Lukaszewski et al 1999;Shurin 2000;De Meester et al 2002;Binks et al 2005). Moreover, dispersal is often haphazard in the sense that only a few colonists are likely to disperse to the same location at any one time, making small colonist populations vulnerable to extinction via Allee effects (Stephens et al 1999;Kramer et al 2008).…”
Section: Introductionmentioning
confidence: 99%